2007
DOI: 10.1002/met.26
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of promulgating higher resolution wind data for airline route planning

Abstract: A study has been undertaken to determine whether there are useable incremental benefits from providing upper air wind data at high horizontal resolution to the process of airline flight planning. Currently winds are provided on a horizontal resolution of approximately 140 km. The study looked at resolutions varying between 160 and 40 km. A theoretical calculation was undertaken using published variance power spectra, which quantify the wind variability as a function of horizontal scale. This calculation also u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…We calculate the latitudinal and longitudinal wind gradients, which feature in the heading equation, using second-order centred differences. Although the GFDLCM2.1 model is coarser in resolution than the models that are used operationally in flight planning, minimum-time routes have been found to display no significant dependence on the horizontal resolution of the ingested wind data, with flight times changing by less than 1 s for a typical transatlantic flight when the resolution is doubled (Lunnon and Mirza 2007). A winter climatology of the minimum-time routes calculated by the algorithm for the pre-industrial control simulation is shown in figure 3.…”
Section: Minimum-time Routesmentioning
confidence: 96%
“…We calculate the latitudinal and longitudinal wind gradients, which feature in the heading equation, using second-order centred differences. Although the GFDLCM2.1 model is coarser in resolution than the models that are used operationally in flight planning, minimum-time routes have been found to display no significant dependence on the horizontal resolution of the ingested wind data, with flight times changing by less than 1 s for a typical transatlantic flight when the resolution is doubled (Lunnon and Mirza 2007). A winter climatology of the minimum-time routes calculated by the algorithm for the pre-industrial control simulation is shown in figure 3.…”
Section: Minimum-time Routesmentioning
confidence: 96%
“…Linear interpolation is then applied to obtain wind components and temperature at specific points in a trajectory. This approach is justified as long haul flight routes have been shown to be largely insensitive to the resolution of weather data (Lunnon and Mirza 2007) and the evolution of the jet stream at this altitude shows little variation across a 24-hour period (Mangini et al 2018). The use of daily wind data is in line with methods used in previous transatlantic trajectory research (Wells et al 2021;Kim et al 2020;Williams 2016;Mangini et al 2018).…”
Section: Data-driven Wind and Temperature Fieldsmentioning
confidence: 99%